Hubungan Motivasi Perawat Dengan Kelengkapan Dokumentasi Asuhan Keperawatan - Setia Wulanningsih, Eka; Lannasari, Lannasari; Mintasih , Sri (The SDGS Forum Communication, 2024)
Nursing care is one indicator in determining the quality of service from a hospital. One of the most important aspects of performance is the documentation of nursing care. Motivation is needed by nurses in documenting nursing care in hospitals, achieving high work productivity. The aim of the research was to determine the relationship between nurse motivation and the completeness of nursing care documentation in inpatient care at AZRA Hospital. The research method used is quantitative research with a correlation study design. This study used a cross sectional approach with a total sampling of 69 patients. The statistical test that will be used is chi-square. The research results showed that nurses with high work motivation were 53.7% and 46.3% were low. Incomplete nursing documentation was 26.1%, and 73.9% was complete. The statistical test results obtained a p value of 0.002 (<0.05). The research conclusion is that there is a significant relationship between nurse motivation and the completeness of nursing care documentation in the AZRA Hospital inpatient room. Suggestions, especially the application of motivation in documenting nursing care so that work can be carried out optimally.